Partial characterization of enzymatic activities produced by a wild strain of A. niger - Martos, María Alicia (2012)
Aspergillus niger, isolated from decay citrus peels in the province of Misiones, was able to produce pectinases by submerged fermentation. The enzymatic extract exhibited polygalacturonase, pectinesterase and lyase activities. Others enzymes capable of degrading cell wall polymers were also detected in the enzymatic extract such as cellulases and xylanases. Polygalacturonase was an endo-polygalacturonase. The enzyme exhibited a maximal activity at pH range between 4.5 to 5.0, was stable in the pH range from 2.5 to 5.5 and remained unchanged when was incubated at temperatures lower than 50 ºC. The fungi produced three PG isoenzymes. The enzymatic extract was able to clarify apple juice. The results observed make the pectinolytic enzymes produced by A. niger appropriate for future application in fruit juice processing industries.